A novel balanced isotonic sodium solution vs normal saline during major surgery in children up to 36 months: a multicenter RCT. Issue 9 (14th May 2014) - Disma, Nicola; Mameli, Leila; Pistorio, Angela; Davidson, Andrew; Barabino, Paola; Locatelli, Bruno Guido; Sonzogni, Valter; Montobbio, Giovanni; Anderson, Brian
Summary Background The use of isotonic electrolytic solutions for the intraoperative fluid management in children is largely recognized, but the exact composition still needs to be defined. Objectives The primary objective of this randomized controlled open trial was to compare the changes in chloride plasma concentration using two intraoperative isotonic fluid regimens (Sterofundin vs normal saline, both added with 1% of glucose) in children undergoing major surgery. Secondary objectives were to compare changes in other electrolytes, renal function, and the occurrence of hypoglycemia. Methods Children aged between 1 and 36 months, scheduled for major surgery, were randomized to receive Sterofundin or saline during the intraoperative time. Children with preoperative electrolyte abnormalities, hemodynamic instability, and severe renal or hepatic dysfunction were excluded. The primary outcome was the Δ of Cl− (Δ = change in plasma concentration between post‐ and pre‐infusion), and secondary outcomes included Δ of other electrolytes and intraoperative hypoglycemia. Results A total of 240 patients were included in the two study sites and randomized to receive Sterofundin plus 1% glucose or normal saline plus 1% glucose, in a open fashion (229 were finally analyzed). Δ of Cl− and Mg++ was statistically less relevant in patients who received intraoperative Sterofundin, and Δ of the other electrolytes was comparable between the two study groups. Relative risk of hyperchloremia was significantly higher when large volumes were infused (over than 46.7 ml·kg−1), regardless of type of crystalloid infused. Hypoglycemia occurred in two of 229 patients. Conclusions Sterofundin is safer than normal saline in protecting young children undergoing major surgery against the risk of increasing plasma chlorides and the subsequent metabolic acidosis.